Body shape comparison of Cyprinion macrostomum (Heckel, 1843) and Cyprinion watsoni (Day, 1872) using geometric moprphometrics method - Manoochehr Nasri; Soheil Eagderi; Hamid Farahmand; Iraj Hashemzadeh Segherloo (International journal of aquatic biology, 2013)
This study investigated shape differences in two species of Cyprinion macrostomum from Tigris basin and Cyprinion watsoni from Hormuz basin using discriminate function analysis. Coordinates of 17 external landmark points on 2D pictures were used for the analysis. There were significant differences of the two species. C. macrostomum have longer head length, snout length, preventral distance, head height, body height and length of pectoral fin bases than those of C. watsoni . The caudal peduncle length, caudal peduncle depth and anal fin base length in C. watsoni are longer than those of C. macrostomum , the pectoral fin in C. macrostomum was originated more posteriorly than that C. watsoni . Based on the geometric morphometrics differences, the two species can be well recognized and differentiated.